2021
DOI: 10.1007/s00402-021-04032-6
|View full text |Cite
|
Sign up to set email alerts
|

Subacromial impingement syndrome: association of multiple magnetic resonance imaging parameters with shoulder function and pain

Abstract: Introduction Shoulder pain is one of the most common complaints in orthopaedics. This study focusses on the relationship between shoulder function in subacromial impingement syndrome and imaging criteria in magnetic resonance imaging (MRI). Materials and methods This prospective clinical trial included 69 patients treated for subacromial impingement syndrome. Shoulder function (Constant Score, range of abduction, abduction force) and pain were correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The preferred noninvasive method for assessing shoulder joint injuries is a combination of clinical examination and MRI [ 20 ]. MRI is an excellent tool for evaluating bony, cartilaginous, ligamentous, and synovial diseases, as well as trauma, infection, and malignancy [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The preferred noninvasive method for assessing shoulder joint injuries is a combination of clinical examination and MRI [ 20 ]. MRI is an excellent tool for evaluating bony, cartilaginous, ligamentous, and synovial diseases, as well as trauma, infection, and malignancy [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the many causes of SIS, subacromial spurs are considered one of the main pathologies, and various studies have reported the relationship between SIS and subacromial spurs [6][7][8]. Neer [5,9] described the need for partial anterior acromioplasty by stating that impingement of the RC by subacromial spurs results in RC tears.…”
Section: Introductionmentioning
confidence: 99%
“…La ¨hdeoja [18] reported that spur size did not correlate significantly with shoulder function or pain, which was proposed based on findings that subacromial decompression had no benefit in terms of functional outcome or pain. Ja ¨schke [6] found that shoulder function was not compromised by the presence of a subacromial spur in the absence of bursitis after studying 69 patients treated for SIS. Additionally, it was reported that rather than the type of acromion, other factors might cause impingement in the formation of RC pathology [19][20][21].…”
Section: Introductionmentioning
confidence: 99%